Modern evolution of paper-based analytical devices for wearable use: from disorder to order. Issue 16 (23rd July 2020) - Chu, Tianshu; Chu, Jianlin; Gao, Bingbing; He, Bingfang
Abstract : The modern evolution of paper-based analytical devices is from disorder to order and widely used as wearable sensors. Abstract : Paper devices have attracted great attention for their rapid development in multiple fields, such as life sciences, biochemistry, and materials science. When manufacturing paper chips, flexible materials, such as cellulose paper or other porous flexible membranes, can offer several advantages in terms of their flexibility, lightweight, low cost, safety and wearability. However, traditional cellulose paper sheets with chaotic cellulose fiber constitutions do not have special structures and optical characteristics, leading to poor repeatability and low sensitivity during biochemical sensing, limiting their wide application. Recent evidence showed that the addition of ordered structure provides a promising method for manufacturing intelligent flexible devices, making traditional flexible devices with multiple functions (microfluidics, motion detection and optical display). There is an urgent need for an overall summary of the evolution of paper devices so that readers can fully understand the field. Hence, in this review, we summarized the latest developments in intelligent paper devices, starting with the fabrication of paper and smart flexible paper devices, in the fields of biology, chemistry, electronics, etc . First, we outlined the manufacturing methods and applications of both traditional cellulose paper devices and modern smart devices based on pseudopaper (order paper). Then, considering different materials, such as cellulose, nitrocellulose, nature sourced photonic crystals (photonic crystals sourced from nature directly) and artificial photonic crystals, we summarized a new type of smart flexible device containing an ordered structure. Next, the applications of paper devices in biochemical sensing, wearable sensing, and cross-scale sensing were discussed. Finally, we summarized the development direction of this field. The aim of this review is to take an integral cognition approach to the development of smart flexible paper devices in multiple fields and promote communications between materials science, biology, chemistry and electrical science.